Bioactive sesquiterpene pyridine alkaloids from Maytenus aquifolium - Corsino, J.; Bolzani, Vanderlan da Silva [UNESP]; Pereira, AMS; Franca, S. C.; Furlan, Maysa [UNESP] (Elsevier B.V., 1998)
Two new sesquiterpene evoninate alkaloids, were isolated together with the known compounds syringaresinol and 4'-O-methyl-(-)-epigallocatechin from the root bark of Maytenus aquifolium. The structures of the two alkaloids were elucidated by interpretation of their spectral data, and both exhibited very weak activity in a mechanism-based DNA-modifying yeast assay. (C) 1998 Elsevier B.V. Ltd. All rights reserved.
Keywords: Maytenus aquifolium; Celastraceae; root bark; sesquiterpene evoninate alkaloids